2020
DOI: 10.3390/cancers12092396
|View full text |Cite
|
Sign up to set email alerts
|

Implications of CLSPN Variants in Cellular Function and Susceptibility to Cancer

Abstract: Claspin is a multifunctional protein that participates in physiological processes essential for cell homeostasis that are often defective in cancer, namely due to genetic changes. It is conceivable that Claspin gene (CLSPN) alterations may contribute to cancer development. Therefore, CLSPN germline alterations were characterized in sporadic and familial breast cancer and glioma samples, as well as in six cancer cell lines. Their association to cancer susceptibility and functional impact were investigated. Eigh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 66 publications
1
6
0
Order By: Relevance
“…To thoroughly understand the features of CLSPN, we further explored its alterations utilizing cBioPortal database. Among these alterations, we observed missense mutation as the commonest type, while inframe mutation was the rarest, which was consistent with the research of other scholars [ 44 , 45 ]. Besides, our results revealed that the truncate mutation of R1139*/Q site in CLSPN had the highest frequency, which had never been proved by basic experiments before.…”
Section: Discussionsupporting
confidence: 91%
“…To thoroughly understand the features of CLSPN, we further explored its alterations utilizing cBioPortal database. Among these alterations, we observed missense mutation as the commonest type, while inframe mutation was the rarest, which was consistent with the research of other scholars [ 44 , 45 ]. Besides, our results revealed that the truncate mutation of R1139*/Q site in CLSPN had the highest frequency, which had never been proved by basic experiments before.…”
Section: Discussionsupporting
confidence: 91%
“…Furthermore, SNPs in these regions can alter gene expression or alter gene-molecule interactions leading to complex diseases [16]. A CLSPN mutation c.1574A>G has been demonstrated to reduce CLSPN expression and activate Chk1, which may affect the CLSPN structure and function in breast cancer [25]. There is evidence that CLSPN, which has been found to express the I783S missense mutation that inhibits its ability to mediate Chk1 phosphorylation after DNA damage, may be associated with tumorigenesis [24].…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, elevated expression of CLSPN is closely related to the induction of immune cell infiltration, tumor mutation burden, microsatellite instability, mismatch repair, and DNA methylation in various cancer types [23]. In recent years, researchers have begun to study the role of the CLSPN gene in cancer development, specifically after finding high levels of CLSPN in cancers as diverse as breast, ovarian, cervical, glioma, non-small cell lung cancer and renal cell carcinoma [24][25][26][27][28].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, it is urgent to establish an understanding of the pathogenesis of HCC and to seek effective therapeutic targets. CLSPN, an essential molecule of the S-phase checkpoint in DNA replication stress, has been proven to be involved in the process of cancers (10,21), but its roles in HCC remain ambiguous.…”
Section: Discussionmentioning
confidence: 99%